KONSEP MANAJEMEN SYARIAH PADA BAITUL MAL GAMPONG KECAMATAN BANDA SAKTI KOTA LHOKSEUMAWE - Yunus, Muhammad; Cut Ali, Isnu; Syahriza, Mulkan; Janiati, Cut (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2023)
Each Baitul Mal Gampong must manage each Baitul Mal Gampong fund based on management that is in accordance with the Islamic concept. Each village in Banda Sakti sub-district, Lhokseumawe City has a different management concept in managing Baitul Mal. As for the formulation of the problem in this study are: one. how is the concept of Sharia management at Baitul Mal located in the sub-district in Banda Sakti District, Lhokseumawe City? 2. What are the obstacles in implementing Sharia management at Baitul Mal which is in the Banda Sakti sub-district, Lhokseumawe City. The research method in this writing is a qualitative research method with data collection techniques based on observation, interviews and documentation. The conclusions that the authors can obtain in this study are as follows: one concept of Sharia management, even in villages located in the sub-district of Lhokseumawe City, has the concept of planning, organizing implementation, and evaluating. the concept of Sharia management, namely the Kampung Mall is based on 5 principles, namely the principles of monotheism, caliph, justice, Ukhuwah and Maslahah. be it village malls that apply sharia management concepts that do not fully apply sharia management concepts, namely Gampong Ujung Blang and Gampong Pusong Lama. in carrying out the management of Baitul Mal Gampong, namely as follows first, understanding of fiqh by amil does not understand, second, lack of quality human resources, third, the technology used is still low, fourth, lack of public awareness in paying zakat. the lack of public trust in every Baitul Mall village in the Banda Sakti sub-district, Lhokseumawe City